Erliquiose monocítica canina experimental: avaliação de parâmetros clínicos, laboratoriais e imunológicos, antes e após o cloridrato de tetraciclina - Simone Magela Moreira (2005)
One of the main goals of research on canine monocytic ehrlichiosis has been to clarify the clinical and hematological alterations, as well the immunological mechanisms, involved on the pathogenesis of the disease. In the daily veterinary practice, it can be observed that tratments instituted during the acute phase promote fast improvement of the animal clinical conditions. In the presented study, nine dogs were experimentally infected with Ehrlichia canis (Jaboticabal strain) and were treated with tetracycline hydrochloride (22mg/kg/per day) for 21 days, beginning at the thirtirth day after infection. Some clinical, hematological and immunological parameters were evaluated during the acute phase of the disease and after the treatment. In addition, their immune responses were evaluated before and after the treatment by citometric analyses and cell phenotype (FACS) using monocional antibodies to cell surface markers for CD, Thy-1, CD4, CD14, MHC II, CD45R, and IgM.